The Contexts of Indigenous Music Activity in the Kimberley: Pedagogic Models for Aboriginal Music - Dunbar-Hall, Peter (The Australian Journal of Indigenous Education, 2001)
In response to documented problems in the teaching of Australian Indigenous music in schools, this paper proposes the use of the contexts of music as the bases of pedagogic models. In relation to Indigenous music activity in the Kimberley region of north-west Australia, four contexts are explained and their potential to provide ways of studying Indigenous music is explored: Kimberley Indigenous music in relation to national Aboriginal music music and history music and place music and politics While these contexts provide relatively simple ways of structuring pedagogies for Indigenous music, their potential to represent the symbolic levels of music as expression of cultural concerns bay be their real significance in the attempt to utilise Indigenous music in music education.